Resveratrol mediates therapeutic hepatic effects in acquired and genetic murine models of iron‐overload. (3rd July 2015) - Das, Subhash K.; DesAulniers, Jessica; Dyck, Jason R. B.; Kassiri, Zamaneh; Oudit, Gavin Y.
Abstract: Background & Aims: Abnormal iron metabolism and hepatic iron‐overload is a major cause of liver injury and in the development of chronic liver diseases. Iron‐overload‐mediated liver disease leads to end‐stage cirrhosis and/or hepatocellular carcinoma. Methods: Using a genetic hemochromatosis (hemojuvelin knockout mice) and non‐genetic (secondary iron‐overload) murine models of hepatic iron‐overload, we elucidated the mechanism of hepatic iron injury and the therapeutic effects of resveratrol. Results: Hepatic iron‐overload was associated with hepatosplenomegaly, increased oxidative stress, hepatic fibrosis, and inflammation, and a pro‐apoptotic state which was markedly corrected by resveratrol therapy. Importantly our aging studies with the hemojuvelin knockout mice showed advanced liver disease in association with steatosis in the absence of a diabetic state which recapitulates the essential pathological features seen in clinical iron‐overload. Chronic hepatic iron‐overload showed increased nuclear localization of acetylated Forkhead fox‐O‐1 (FoxO1) transcription factor whereas resveratrol dietary intervention reversed the acetylation of FoxO1 in association with increased SIRT1 levels which together with its pleotropic antioxidant properties are likely key mechanisms of its therapeutic action. Importantly, resveratrol treatment did not affect the degree of hepatic iron‐overload but rather direct protects the liver from iron‐mediated injury. Conclusions: Our findings illustrate a novel and definitive therapeutic action of resveratrol and represent an economically feasible therapeutic intervention to treat hepatic iron‐overload and liver disease.